A robust redox-active hydrogen-bonded organic framework for rechargeable batteries. Issue 4 (5th January 2022) - Liu, Xiaolin; Yang, Xiya; Wang, Hailong; Hisaki, Ichiro; Wang, Kang; Jiang, Jianzhuang
Abstract : A robust HOF has been employed as cathode for LIBs. The decoration of rich redox-active moieties in HOFs introduces the surface-controlled capacitive mechanism in LIBs, accessing a high capacity, high rate capability and excellent cycling stability. Abstract : Problems such as low cycle stability, poor ion mobility and weak conductivity hinder the development of organic electrode materials. Herein, one of the robust porous hydrogen-bonded organic frameworks (HOFs), CPHATN-1a, has been used as a cathode for lithium-ion batteries (LIBs). Redox-active hexaazatrinaphthalene (HATN) moieties were firmly fixed in this HOF by the hydrogen-bonded connection and tight π–π packing, providing a high capacity of 128 mA h g −1 at 0.1C. In addition, this HOF-based LIB is able to deliver a high cycling stability with 102 mA h g −1 after 500 cycles at 1.0C and a good rate capability (78 mA h g −1 at 2.0C). Moreover, the Li storage mechanism associated with the HOF was systematically analysed by electrochemistry, X-ray photoelectron spectroscopy and powder X-ray diffraction. These results indicate the bright perspective of robust HOFs as organic cathode materials for LIBs.